PENGARUH METAPHORICAL THINKING APPROACH BERBASIS PROJECT METHOD TERHADAP LITERASI MATEMATIS DITINJAU DARI GAYA BERPIKIR PESERTA DIDIK - Nurbaiti, Anis; Wahyu Yunian Putra, Rizki; Ulfa Nabila, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the metaphorical thinking approach based on the project method on students’ mathematical literacy in terms of their thinking styles. This research is motivated by the low level of students’ mathematical literacy and the dominance of conventional learning that is less connected to real-life contexts. This study used a quantitative method with a quasi-experimental design and was analyzed using two-way ANAVA. The population consisted of seventh-grade students of SMP Negeri 19 Bandar Lampung, and the sample was selected using cluster random sampling. The instrumens used were a mathematical literacy test and a thinking style questionnaire. The results showed that: there was a significant effect of the metaphorical thinking approach based on the project method on students’ mathematical literacy thinking styles also had a significant effect on mathematical literacy and there was no interaction between the learning approach and thinking styles . Therefore, the metaphorical thinking approach based on the project method can be an effective alternative to improve students’ mathematical literacy.